The effects of COVID-19 lockdown on jumping performance and aerobic capacity in elite handball players - Font, Roger; Irurtia, Alfredo; Gutierrez, Jose; Salas, Sebastià; Vila, Enric; Carmona, Gerard (Biology of Sport, 2021)
The aim of this research was to analyse the capacity of a home-based training programme to preserve aerobic capacity and jumping performance in top-level handball players during the COVID-19 lockdown. Eleven top-level male handball players from the same team participated in the study. A submaximal shuttle run test and a counter-movement jump test were used to measure the players’ aerobic fitness and lower limb explosive strength, respectively. A 9-week home-based training programme was followed during lockdown. Pre-test measurements were assessed before the pandemic on 29 January 2020 and ended on 18 May 2020. Moderate significant mean heart rate increases were found in the late stages of the submaximal shuttle run test after the lockdown (stage 5, 8.6%, P = 0.015; ES = 0.873; stage 6, 7.7%, P = 0.020; ES = 0.886; stage 7, 6.4%, P = 0.019; ES = 0.827). Moderate significant blood lactate increases were observed immediately after the submaximal shuttle run test following the lockdown (30.1%, P = 0.016; ES = 0.670). In contrast, no changes were found in jump performance. A structured home-based training programme during the COVID-19 lockdown preserved lower limb explosive strength but was an insufficient stimulus to maintain aerobic capacity in top-level handball players